Effectiveness of prenatal yoga in reducing low back pain among pregnant women: A systematic literature review - Ni Nyoman Rai Warsiki; Ni Luh Putu Sri Erawati; Ni Wayan Armini (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Low back pain is one of the most common musculoskeletal complaints experienced during pregnancy, particularly in the second and third trimesters. Physiological and biomechanical changes during pregnancy may impair maternal mobility, daily activities, sleep quality, and overall well-being. Prenatal yoga has been increasingly recommended as a safe non-pharmacological intervention to alleviate pregnancy-related back pain; however, comprehensive evidence regarding its effectiveness remains necessary. Purpose: To systematically identify, evaluate, and synthesize the available evidence regarding the effectiveness of prenatal yoga in reducing low back pain among pregnant women. Method: This study employed a systematic literature review following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature searches were conducted in PubMed, ScienceDirect, Google Scholar, and Garuda databases. Articles published between 2021 and 2025 in English or Indonesian were screened according to predefined inclusion and exclusion criteria. Studies involving pregnant women receiving prenatal yoga interventions with back pain as an outcome were included. Ten eligible studies consisting of randomized controlled trials, quasi-experimental studies, and systematic reviews were analyzed narratively. Results: The findings consistently demonstrated that prenatal yoga effectively reduced the intensity of low back pain among pregnant women. The intervention improved muscle flexibility, posture, balance, and physical function while decreasing muscle tension. In addition to pain reduction, prenatal yoga contributed to better sleep quality, lower stress and anxiety levels, enhanced relaxation, and improved maternal quality of life during pregnancy. Conclusion: Prenatal yoga is an effective, safe, and feasible complementary intervention for reducing low back pain during pregnancy, particularly in the second and third trimesters. Incorporating prenatal yoga into routine antenatal care may improve both physical and psychological well-being among pregnant women.